CHINESE LACQUERWARE AND DESIGN DIMENSIONS OF CONTEMPORARY LACQUERWARE - Zhao, Junguo; Puntien, Pisit; Phuangsua, Kanyanee (FOCUS ON ARTS : FAR, SSRU, 2024)
The objectives of this research were 1) Study the patterns and techniques of lacquerware in Chinese culture, as well as the production methods of traditional lacquerware. 2) Analyzing the technological factors in the development of contemporary Chinese lacquerware product design, 3) Contemporary lacquerware design reflects the inheritance culture of pattern culture and contemporary technology. Using qualitative research methods, operate by studying the information in the references. Field investigation, including participant observation and non-participant observation, expert interviews, and analysis of design data through descriptive analysis. The results indicate that the modernization of contemporary lacquerware represents significant progress in the utilization of irreplaceable raw materials such as raw lacquer. The complex and time- consuming lacquerware process requires precise refinement, which machines cannot replace. This aspect is crucial for protecting tradition, as it can be strengthened but will never be replaced. In the development process of lacquerware, these challenges were encountered because its creation is essentially product design. However, unique materials and processes often obscure its purpose, leading people to overlook its practical functions. Previous lacquerware works mainly focused on artistic forms or craftsmanship, emphasizing the display of their identity. However, as a product, its functionality holds significant importance. If we only focus on materials, processes, and other performance aspects, we may lose the true essence of product design. Therefore, the development of contemporary lacquerware needs to focus on practicality and functionality, reflecting the demands and current trends in this field.